The tradeoff between data granularity and storage costs - Pereira, Inês Correia (2021)
In the increasinglytechnology-dependent world, data is one of the key strategic resources for organizations. Often, the challengedecision-makers face is to determine how much data to collect and store. In this thesis, this challenge is studied in the context of a collection of mobile signaling data for studying tourists’ behavioral patterns.The objective is to analyze to what extent can individual trajectories be reconstructed if only a fraction of the original location data is preserved, providing insights about the tradeoff between the volume of data available and the accuracy of reconstructed paths.